Historical record on the Brazilian hawkmoths (Lepidoptera: Sphingidae) deposited in the Entomological Collection of the Museu de História Natural da Bahia (MHNBA) in Salvador, Bahia, Brazil - Ramos, Ramon Lima; Lopes, Daniele Santos; Garcia, Caroline Tito; Trindade-Santos, Matheus Eduardo; Oliveira, Favízia Freitas de (EntomoBrasilis, 2021)
In this article we present the historical records of the Brazilian hawkmoths deposited in the Entomological Collection of the Museu de História Natural da Bahia (MHNBA-UFBA), including the historical Lepidoptera collection donated by Dr. Pedro de Araújo to the MHNBA-UFBA. The Sphingidae collection is composed of 243 specimens and represents 24 genera and 66 species. The historical collection consists of specimens captured between the years 1924 and 1934, and we also included to the collection specimens that were captured more recently, between 1982 and 2014. The subfamily Macroglossinae presented the greatest species richness and Smerinthinae the presented the least species richness. Of all of specimens in the collection, 151 came from São Paulo State (Brazil), 41 from Santa Catarina State, 50 from Bahia State and only one from Pernambuco State. Three topotypes were identified in the collection, namely: Eumorpha translineatus (Rothschild, 1895), Xylophanes crenulata Vaglia & Haxaire, 2009 and Xylophanes alineae Haxaire & Mielke, 2018.